Visual Representations of Sexual Violence in Online News Outlets - Schwark, Sandra (Frontiers in Psychology, 2017)
To study visual representations of sexual violence, photographs accompanying German Internet news articles that appeared between January 2013 and March 2015 (N = 42) were subjected to thematic analysis. Two main themes, consisting of several sub-themes, emerged from the data. The first theme was ‘rape myths’, illustrating a stereotypical view of sexual violence. It consisted of three sub-themes: ‘beauty standards’, referring to the fact that all women in our sample fit western beauty standards, ‘physical violence’, as most images implied some form of physical violence, and finally ‘location’, suggesting that rape only happens in secluded outdoor areas. These findings suggest that the images from our sample perpetuate certain rape myths. The second theme was ‘portrayal of victimhood’, referring to the way victims of sexual violence were portrayed in photographs. The analysis of the sub-theme ‘passivity’ showed that these portrayals fit a certain stereotype: the women were shown to be weak and helpless rather than individuals with agency and able to leave their status as a victim. Further sub-themes were ‘background’, ‘organization of space’, ‘camera perspective’ and ‘lighting’. We discuss these findings in relation to possibly reinforcing rape myths in society and as an issue in creating a biased perception of women who have experienced sexual violence.